Catheter ablation of atrial fibrillation in heart failure with impaired systolic function: An updated meta-analysis of randomized controlled trials. Issue 1 (13th October 2022) - Chang, Ting-Yung; Chao, Tze-Fan; Lin, Chin-Yu; Lin, Yenn-Jiang; Chang, Shih-Lin; Lo, Li-Wei; Hu, Yu-Feng; Chung, Fa-Po; Chen, Shih-Ann
Abstract : Background: The recent Atrial Fibrillation Management in Congestive Heart Failure With Ablation trial did not reveal any benefit of catheter ablation in patients with atrial fibrillation (AF), advanced heart failure (HF), and severely reduced left ventricular ejection fraction (LVEF). We hypothesized that radiofrequency catheter ablation (RFCA) could improve outcomes in HF patients with AF and impaired left ventricular systolic function (LVEF <50%) as compared with only medical therapy. Methods: We searched the literature for randomized clinical trials (RCTs) that compared RFCA to medical therapy in this population. Results: Compared with the medical therapy group, the RFCA group had significantly less all-cause mortality, HF hospitalization, and AF recurrence rates. The RFCA group had significantly higher peak oxygen consumption (VO2max ), a better quality of life (Minnesota Living with Heart Failure Questionnaire score), and improved LVEF. However, RFCA for AF failed to reduce all-cause mortality in a specific meta-analysis of four RCTs that enrolled patients with LVEF ≤35%. Conclusion: Compared with medical therapy, RFCA for AF in the setting of HF with impaired systolic function is associated with better clinical (HF hospitalization and all-cause mortality), structural (LVEF improvement), functional (VO2max ), and quality of life outcomes. However, RFCA for AF failed to reduce all-cause mortality in RCTs that enrolled patients with LVEF ≤35% and thereby indicated the necessary stratification to identify patients who may benefit more from RFCA.